Breaking down the complement system: a review and update on novel therapies. Issue 2 (March 2017) - Reddy, Yuvaram N.V.; Siedlecki, Andrew M.; Francis, Jean M.
Abstract : Purpose of review: The complement system represents one of the more primitive forms of innate immunity. It has increasingly been found to contribute to pathologies in the native and transplanted kidney. We provide a concise review of the physiology of the complement cascade, and discuss current and upcoming complement-based therapies. Recent findings: Current agents in clinical use either bind to complement components directly or prevent complement from binding to antibodies affixed to the endothelial surface. These include C1 esterase inhibitors, anti-C5 mAbs, anti-CD20 mAbs, and proteasome inhibitors. Treatment continues to show efficacy in the atypical hemolytic uremic syndrome and antibody-mediated rejection. Promising agents not currently available include CCX168, TP10, AMY-101, factor D inhibitors, coversin, and compstatin. Several new trials are targeting complement inhibition to treat antineutrophilic cystoplasmic antibody (ANCA)-associated vasculitis, C3 glomerulopathy, thrombotic microangiopathy, and IgA nephropathy. New agents for the treatment of the atypical hemolytic uremic syndrome are also in development. Summary: Complement-based therapies are being considered for targeted therapy in the atypical hemolytic uremic syndrome and antibody-mediated rejection, C3 glomerulopathy, and ANCA-associated vasculitis. A few agents are currently in use as orphan drugs. A number of other drugs are in clinical trials and, overall, are showing promising preliminary results.